Contratos coligados na distribuição de combustível: relação entre distribuidora e revendedor de bandeira - Tavares, Beatriz Cal (2023)
Based on the doctrinal perception of the relevance of contractual combinations to the reality of inter-company operations, studies have been developed regarding related contracts. In view of this, the relationship between the distributor and the flagged fuel reseller is evidenced, which may be composed of several autonomous contracts aimed at a common purpose. Thus, the work studies this relationship from the perspective of contractual coalition, to assess the grounds for identifying them as related and their implications. In this sense, initially, the theory of related contracts is presented, exposing its characteristics and effects. In view of the above, in the light of doctrinal and jurisprudential studies on the subject, we discuss the reasons for identifying the contractual coalition between the distributor and the flagged fuel reseller. In this regard, the most common contracts and the causes of their termination are exposed, analyzing whether there is a spread of invalidity and ineffectiveness between such contracts. Aiming at an ideal treatment, the role of interpretation in these contracts is elucidated. And given the individuality of the contracts, the study outlines whether the derogation of the typical effects is an effective measure for the purpose of better treating them. Finally, the coalition is related to the principle of conservation of legal business, aiming to identify the effects of its application in the contractual relationship under study